Analyzing the encoding-decoding of the transnational audiovisual discourse of ISIS in Netflix’s caliphate - al-Sayih, Muhammad Ibrahim Muhammad Ibrahim (Transcultural Journal of Humanities and Social Sciences, 2023)
Reception studies have become an essential element in the audiovisual translation research. in fact, the transnational turn in the study of media audiences has led to a reciprocity between reception studies and audiovisual translation research. this study aims at conducting a semiotic analysis of the Arab viewers’ reception of the Arabic subtitling of Netflix’s Swedish series caliphate. hence, the study poses the question of how the Arab audience incorporate the dominant audiovisual discourse about ISIS, which is semiotically encoded by Netflix through the medium of subtitling. to better understand Netflix’s dominant ISIS discourse, the study examines the socio-political context involved in the framing of this televised discourse. the study is product-oriented since it investigates the reception of Netflix’s ISIS audiovisual discourse by transnational audience. this investigation is conducted through applying hall’s (1973) encoding / decoding model. the model assesses how audiences play an active role in decoding the media messages and discourses that target them. decoding takes place within a milieu of ideological, political, social and economic contexts. the interplay between these contexts defines how audiences can choose to either incorporate or to resist the ideologically-driven messages delivered to them in the form of audiovisual discourses. this study proves that as part of the broader transnational audience, Arab audience subscribes to a preferred reading of the ISIS audiovisual discourse formed by Netflix.